2003
DOI: 10.1046/j.1528-1157.2003.34703.x
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Spasms in a Patient with Williams Syndrome and Craniosynostosis

Abstract: Summary:  A patient with Williams syndrome, craniosynostosis, and infantile spasms is described. At age 6 months, the infant demonstrated infantile spasms and craniosynostosis and was operated on for craniosynostosis and treated with adrenocorticotropic hormone (ACTH) for the infantile spasms. ACTH completely controlled the seizures, but was halted because of the progression of ventricular hypertrophy. The seizure returned, and he was found to have elfin face, failure‐to‐thrive, developmental delay, and dental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 15 publications
(19 reference statements)
1
33
0
Order By: Relevance
“…The range of this deletion is exactly same as that of the patient reported by Morimoto et al who also showed infantile spasms and cardiomegaly (Morimoto et al, 2003) (see Fig. 5).…”
Section: Figsupporting
confidence: 86%
See 3 more Smart Citations
“…The range of this deletion is exactly same as that of the patient reported by Morimoto et al who also showed infantile spasms and cardiomegaly (Morimoto et al, 2003) (see Fig. 5).…”
Section: Figsupporting
confidence: 86%
“…This indicates that the infantile spasms and the cardiomegaly observed in patient 2 might be derived from haploinsufficiency of YWHAG, because the WBS patient reported by Morimoto et al (2003). also showed infantile spasms and cardiomegaly.…”
Section: Figmentioning
confidence: 76%
See 2 more Smart Citations
“…Three genes-MAGI2 (MIM: 606382), HIP1 (MIM: 601767), and YWHAGhave been suggested as possible candidates for these atypical features. [46][47][48][49][50][51][52][53] Ramocki et al 51 suggested that haploinsufficiency of HIP1 is sufficient to alter neuronal homeostasis and cause focal and generalized epilepsies and cognitive dysfunction. However, their findings do not exclude the possibility that YWHAG loss of function is sufficient to cause neurological phenotypes alone, as proven by our results.…”
mentioning
confidence: 99%